PENERAPAN TEKNIK MEMBACA SQ3R PADA TATA SURYA DI SMP DALAM MEREMEDIASI MISKONSEPSI SISWA - Syafariani, Sri; Djudin, Tomo; Mahmuda, Diah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was aimed to known effectiveness the SQ3R reading technique to remediate students? misconceptions on solar system in SMP Negeri 4 Pontianak. Sample of this research was students? from 7th grade (N=32). Diagnostic test which consisted 10 three tier multiple choice test used to known students? conceptions. Based on the result of data analysis found the average decrease of students? that misconceptions after being given remedial learning equal to 33%. The result of McNemar test shown there was significant conceptual change  (?2hitung = 51,17; df = 1; ? = 0,05). The average of gain value was ?g?=0,58 (medium). It is expected that SQ3R reading technique can be used as an alternative remediation activities to overcome students? misconceptions. Kata Kunci: Miskonsepsi, Remediasi, SQ3R, Tata Surya